Missing mummy by Ron Roy; illustrated by John Steven Gurney - Roy, Ron; Gurney, John, ill. (New York Random House, 2001)
Dink, Josh, and Ruth Rose help catch the thieves who have stolen the treasure from the museum's mummy exhibit.
A Stepping Stone book.
Keywords: Mystery and detective stories; Stealing-Fiction